PENERAPAN ATTRIBUTE SAMPLING PADA PENGUJIAN KEPATUHAN STRUKTUR PENGENDALIAN INTERN TERHADAP TRANSAKSI PEMBELIAN (Studi Kasus Hotel Sahid Raya Yogyakarta) - Meldawati, Lucyani (Prodi Akuntansi FEB UNITOMO, 2017)
AbstractThis study aims to determine whether the structure of internal control of purchase transactions at Hotel Sahid Raya Yogyakarta is adequate and in the implementation has been obeyed. The research method used in the research to find out is adequate or not is by interview, inspection, and observation. Compliance testing is performed with a stop-or-go sampling model.The results obtained from this study are: First, based on the results of interviews and observations obtained components internal control structure of purchase transactions at Hotel Sahid Raya Yogyakarta has been adequate.Secondly, based on the compliance test, it is found that the internal control structure of the purchase transaction at Hotel Sahid Raya Yogyakarta has been complied with.Â Keywords: internal control structure, controlling test, stop-or-go sampling